2017
DOI: 10.1038/s41598-017-13902-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of old RHDV strains by complete genome sequencing identifies a novel genetic group

Abstract: Rabbit hemorrhagic disease (RHD) is a veterinary disease that affects the European rabbit and has a significant economic and ecological negative impact. In Portugal, rabbit hemorrhagic disease virus (RHDV) was reported in 1989 and still causes enzootic outbreaks. Several recombination events have been detected in RHDV strains, including in the first reported outbreak. Here we describe the occurrence of recombination in RHDV strains recovered from rabbit and Iberian hare samples collected in the mid-1990s in Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 56 publications
2
17
0
Order By: Relevance
“…This suggests that these are G1/RHDV2 recombinants, which is in line with the results of previous studies (Mahar et al, 2016;Lopes et al, 2018;Silverio et al, 2018). Genetic variations of 7.0-10.5% of the remaining strains (CB194Pt, CB147 Pt, Eisenhuettenstadt, SD, AST89) in this group, supported by the results of studies by other authors (Abrantes et al, 2012;Lopes et al, 2017), indicate that these are the G1-non-recombinant strains, both within the studied polymerase gene and in the VP60 and VP10 genes . Genetic variability of 14.7% and 14.8% in the RdRp gene was observed in the case of Portuguese strains P95 and P19, which may have been the source of a new variant of polymerase which did not stabilize in the environment.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This suggests that these are G1/RHDV2 recombinants, which is in line with the results of previous studies (Mahar et al, 2016;Lopes et al, 2018;Silverio et al, 2018). Genetic variations of 7.0-10.5% of the remaining strains (CB194Pt, CB147 Pt, Eisenhuettenstadt, SD, AST89) in this group, supported by the results of studies by other authors (Abrantes et al, 2012;Lopes et al, 2017), indicate that these are the G1-non-recombinant strains, both within the studied polymerase gene and in the VP60 and VP10 genes . Genetic variability of 14.7% and 14.8% in the RdRp gene was observed in the case of Portuguese strains P95 and P19, which may have been the source of a new variant of polymerase which did not stabilize in the environment.…”
Section: Discussionsupporting
confidence: 91%
“…Phylogenetic analysis by Lopes and others (Lopes et al, 2017) showed that in the region of the genome encoding structural proteins VP60 and VP10, the strains were similar to pathogenic strains from the GI.1b group (G1), but in the region of the genome that encodes non-structural proteins they had created a new group which was 13% divergent from known strains. According to Lopes and others (Lopes et al, 2017), there are no further reports of this strain surviving in the environment. The absence of information could be due to limited sampling .…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The virus that recombined with GI.3 to produce this new genotype is currently unknown and undetected, even with the molecular surveys of lagoviruses performed in European leporids and our improved knowledge of the complete coding sequences of both pathogenic and benign lagoviruses. The same occurs for some older recombinant Iberian strains where the virus that originated the non-structural part has never been detected 51 . Both viruses, the one originating GI.2 and the one of these Iberian strains, could have either circulated harmlessly prior to their detection, thus making difficult to detect them, or have become extinct due to their lower fitness as a non-recombinant form, as suggested for noroviruses that recombined and whose partial sequences were never found 52 .…”
Section: Discussionmentioning
confidence: 57%